Metalliferous Coals of Cretaceous Age: A Review; Minerals; Vol. 12, iss. 9 - Dai Shifeng; Arbuzov S. I. Sergey Ivanovich; Chekryzhov I. Yu. Igor Yurjevich; French D. David; Feole I. Ian; Folkedahl B. S. Bruce; Graham I. T. Ian; Hower J. C. James; Nechaev V. P. Viktor Petrovich; Wagner N. J. Nicola; Finkelman R. B. Robert (2022, 2022)
Title screen